Structure and function of lamins: norm and pathology - Забірник, А. С.; Костарєва, А. О.; Малашичева, А. Б.; Омельченко, О. А.; Перський, Є. Е. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
Lamins are proteins belonging to the intermediate filaments and forming a "nuclear cytoskeleton" – lamina. This review presents the current understanding of the structure and functions of lamins in health and disease. Most attention is paid to lamin A as more important in terms of the development of pathologies and the variety of functions. Particular place is set aside for molecular mechanisms of pathologies resulting from mutations in the lamin proteins, and lamin role in the differentiation and functioning of stem cells.